Architectural Laboratories - Derya Uzal; Aslıhan Şenel (Enquiry: The ARCC Journal of Architectural Research)
This paper examines the emerging role of the laboratory in architecture, investigating how the "lab" framework has transcended its traditional scientific connotations to become integral to creative, practice-based fields. Historically understood as a controlled environment for producing reliable scientific facts, the laboratory has now been appropriated in interdisciplinary contexts, particularly in architecture, where the focus extends beyond the replication of scientific methods to the development of new research methodologies. This shift has been driven by architecture's inherent dualities—science vs. art, theory vs. practice, and living vs. non-living—compounded by increasing complexity in production. Through an exploration of laboratories in universities in detail the paper situates architecture within a possibility of a new practice supported by research. By engaging with thinkers like Bruno Latour, Karen Barad, and Bernard Stiegler, this study highlights the dynamic possibilities of architectural practice when rethinking material agency, data, and human/non-human relationships. It argues that architecture’s appropriation of the lab framework reflects a deeper engagement with the performative systems of matter, technology, and epistemology. Furthermore, the paper underscores the necessity of reconfiguring architectural practice to address contemporary challenges, by fostering new forms of action that transcend conventional boundaries of laboratory. Ultimately, this paper reveals how the laboratory in architecture is not merely a space for the application of scientific methods but a fertile ground for speculative practices and experimental methodologies that challenge established epistemological frameworks. Through this lens, the architect-agent becomes a connector, facilitating a process that resists total control and embraces open-ended, interactive systems, contributing to the creation of new forms of knowledge and practice.